Evaluating public posting, goal setting, and rewards to increase physical activity during school recess. (22nd May 2018) - Miller, Bryon G.; Valbuena, Diego A.; Zerger, Heather M.; Miltenberger, Raymond G.
Abstract : We evaluated a pedometer‐based intervention consisting of public posting between two teams of students, with additional self‐monitoring, goal setting, and reinforcement components, to increase physical activity during school recess. In the absence of self‐monitoring, performance feedback alone did not increase physical activity levels above those observed during baseline. Additionally, higher levels of physical activity were observed when goal‐setting was introduced, with the highest levels of activity observed when raffle tickets could be earned for exceeding a specified step‐total goal.